2010
DOI: 10.1007/jhep09(2010)053
|View full text |Cite
|
Sign up to set email alerts
|

Neural network parameterizations of electromagnetic nucleon form-factors

Abstract: Abstract:The electromagnetic nucleon form-factors data are studied with artificial feed forward neural networks. As a result the unbiased model-independent form-factor parametrizations are evaluated together with uncertainties. The Bayesian approach for the neural networks is adapted for χ 2 error-like function and applied to the data analysis. The sequence of the feed forward neural networks with one hidden layer of units is considered. The given neural network represents a particular form-factor parametrizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 84 publications
1
36
0
Order By: Relevance
“…The resulting radii, for three different values of q max , are plotted in Figure 11 as a function of the evidence. The density, calculated from the coefficients given in [106] (q max ∼ 10 fm −1 ), is well behaved and out to 2.7 fm very close to the MD and SOG densities (to be shown in Figure 12), which include a physics constraint at large r. From these values, the authors extract the charge-rms radius, which for the three values of q max of Figure 11 [97]. The points in black are corrected for the effects of two-photon exchange.…”
Section: R From Bayesian Inferencementioning
confidence: 99%
“…The resulting radii, for three different values of q max , are plotted in Figure 11 as a function of the evidence. The density, calculated from the coefficients given in [106] (q max ∼ 10 fm −1 ), is well behaved and out to 2.7 fm very close to the MD and SOG densities (to be shown in Figure 12), which include a physics constraint at large r. From these values, the authors extract the charge-rms radius, which for the three values of q max of Figure 11 [97]. The points in black are corrected for the effects of two-photon exchange.…”
Section: R From Bayesian Inferencementioning
confidence: 99%
“…This approach has already been adapted to approximate the electromagnetic nucleon FFs [27] and, here, it is developed to study the TPE effect. The BF was designed to:…”
Section: Bayesian Frameworkmentioning
confidence: 99%
“…This property only seems to be approximate, but we use it to reduce the number of regularization parameters to three. Eventually, we noticed that in our previous paper, it was shown that it was enough to consider one regularization parameter to fit the FF data [27]. Hence, to simplify the numerical calculations and also to accelerate the training process (more than 45 000 training processes have been performed), we consider the simplest regularization scenario with one α parameter.…”
mentioning
confidence: 99%
“…[24] to extract the proton radius from scattering data is described in more detail in Refs. [27][28][29]. In this approach the electric and magnetic form factors are simultaneously parametrized by one feed-forward neural network (with one hidden layer of units) with two outputs:1 A^/(G2;[m,■}) = (««.…”
Section: Bayesian Analysis and Numerical Resultsmentioning
confidence: 99%